2014
DOI: 10.1002/ejic.201402032
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Chloro and Triflate Manganese(II) Complexes in Epoxidation Reactions: Reusable Catalytic Systems for Alkene Epoxidation

Abstract: The catalytic oxidation of a series of alkenes by three MnII complexes, MnCl2[(-)-L]2 (1), ({MnCl[(-)-L]}2(-Cl)2) (2), and Mn(CF3SO3)2[(-)-L]2 (3), having the bidentate N-ligand (-)-pinene[5,6]bipyridine, (-)-L, and using peracetic acid as oxidant in acetonitrile is described. The performance of catalysts 1 and 2 is enhanced by the use of additives (NaHCO3 and imidazole) and also using a [bmim]/acetonitrile mixture as reaction media. The latter conditions allow recyclability of the catalytic system, keeping go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The steric conguration of Mn salen complex plays a signicant role in determining the enantioselectivity of the catalytic process. [1][2][3][4][5][6][7]45 It is interesting to nd that, though the volumes of these anions (Cl À , AcO À , NO 3 À , BF 4 À , and…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steric conguration of Mn salen complex plays a signicant role in determining the enantioselectivity of the catalytic process. [1][2][3][4][5][6][7]45 It is interesting to nd that, though the volumes of these anions (Cl À , AcO À , NO 3 À , BF 4 À , and…”
Section: Resultsmentioning
confidence: 99%
“…The asymmetric epoxidation of olens is an extremely important and powerful reaction for the synthesis of chiral intermediates in the pharmaceutical and agrochemical elds. [1][2][3][4][5][6][7] Jacobsen et al had reported that chiral Mn(III) salen complexes with chloride ions connecting to the mental center could efficiently catalyze the asymmetric epoxidation of olens. [8][9][10][11][12][13][14] As a kind of homogeneous catalysts, chiral Mn(III) salen complexes show quite good catalytic activity and enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of catalytic performance with the use of additives has already been stated for analogous catalytic Mnbased systems. This positive effect is, in some cases (when using peracids as oxidant), related to an increase in the pH value [32,39] that may lead to longer half-life of the intermediate species formed, [40] although coordination of additives to Mn prior to the oxygen transfer step (leading to alternative, more effective intermediate species) has also been postulated. [41,42] In our case, the significant increase in the selectivity when using either imidazole or sodium hydrogen carbonate indicates that the mechanistic pathway leading to the epoxide should be favored with respect to alternative undesired routes and thus the additives might have an active role in determining which mechanistic path is preferred.…”
Section: Catalytic Epoxidation Of Alkenesmentioning
confidence: 94%
“…A similar behavior was observed when related Mn catalysts also bearing pinene type ligands were used. [32,39] In most cases the use of ten equivalents of an additive such as imidazole or NaHCO 3 remarkably increased the conversion, especially when sodium hydrogen carbonate was used. The selectivity for the epoxide product was also increased to a similar extent for both types of additive.…”
Section: Catalytic Epoxidation Of Alkenesmentioning
confidence: 99%
“…The lack of reversibility of the oxidation process, even at higher scan rates, is probably due to solvation and loss of bound chloride in the oxidized complex. It is known that the value of the redox potential of the Mn(II)/Mn(III) couple of chloro-Mn(II) complexes with polyamino/pyridine ligands is 0.3-0.5 V less positive than the solvato-Mn(II) complex formed by ligand exchange of chloride and a solvent molecule [32,[60][61][62]. The observation of a decrease in the intensity of the anodic wave at 1.01 V after the addition of excess AgNO 3 to the complex solution suggests this wave corresponds to the oxidation of [Mn(II)(pypapn)Cl(solv)] + to [Mn(III)(pypapn)Cl(solv)] 2+ , while the oxidation of the solvated complex is outside the scanned potential window.…”
Section: Electrochemical Studiesmentioning
confidence: 99%